BUDAYA SEKOLAH DAN PEMBINAAN AKHLAK SISWA SMP AL-KAUTSAR TANJUNGPINANG - Ramandha Rudwi Hantoro (TANJAK, 2021)
This study aims to determine the relationship between the influence of school culture on the moral development of students at SMP Al-Kautsar, Tanjungpinang City. The population in this study were all students of SMP BP Al-Kautsar Tanjungpinang by taking all students as respondents, totaling 100 students. This research data collection method using questionnaire data and interviews. The hypothesis of this study is that there is a significant relationship between school culture (x) and Moral Development (Y). The results showed that there was a positive influence (0, 481) with a "strong" power (0, 694) at the 5 percent level of confidence between school culture and student morals. Therefore, it can be said that the character building of students is determined by the culture that is formed in the school. The conclusion obtained shows that there is a significant relationship between school culture and student morals at SMP Al-Kautsar Tanjungpinang.